Implementasi Algoritma K-Nearest Neighbor(K-NN) Dalam Klasifikasi Kredit Motor - Efori Bu’ulolo; Irma Suryani Tampubolon; Christin Vebiola Nababan; Lulu Nurhidayanti Nasution (Bulletin of Information System Research, 2022)
Determining the eligibility of applying for a motorbike loan to a leasing company is important, considering that if an error in decision making occurs it will have an impact on the loss of the FIF Group company. Therefore the authors created a Decision Support System using the K-nearest Neighbor method to determine the feasibility of applying for a motorcycle loan. The K-Nearest Neighbor (K-NN) algorithm is an algorithm in data mining to classify new objects based on the majority of the nearest neighbor categories. The K-NN clustering algorithm using data on income, employment, number of dependents and home ownership can group prospective new creditors to make it easier for staff to determine acceptance of prospective new motorcycle creditors